Feasibility of Using Sequential Sulfurized Nanoscale Zerovalent Iron-Persulfate Process to Degrade Tetrabromobisphenol A. (13th September 2021) - Quoc, Tuan Nguyen; Nguyen, Khanh Hoang; Thuy, Huong Ngo Thi; Tien, Nguyen Thi Hanh; Minh, Chau Tran Thi; Dao, Van-Duong; Le, Thao Thanh
Abstract : This study proposed a sequential redox process to partially degrade tetrabromobisphenol A (TBBPA) within a reactor to a great extent. After 72 hours in an anoxic environment, 20 ppm of TBBPA could be effectively degraded by sulfurized zerovalent iron nanoparticles (S-nZVI) at concentrations of 2 g L -1 and 4 g L -1 . Biphenol A (BPA) together with tri-, di-, and monobromobisphenol A was detected by high-performance liquid chromatography (HPLC) suggesting that TBBPA was debrominated by S-nZVI in a stepwise manner. Following the S-nZVI treatment, a persulfate-advanced oxidation process (PS-AOP) system with persulfate concentrations varied from 5 to 20 mM was incorporated to degrade the final debrominated byproduct, BPA, for 2 hours. The two-stage anoxic/oxic reactions at the same reactor with initial conditions (0.037 mM TBBPA, 4 g L -1 of S-nZVI, pH 6 in anoxic stage, 20 mM of PS in the latter oxic stage) were investigated. The sulfurized layer played an important role in such a system and hypothetically contributes to increasing electron transfer from Fe 0 core as well as hydrophobicity of the NP surface. It was demonstrated that the S-nZVI/PS-AOP system could effectively remediate TBBPA and BPA and consequently provide a promising strategy to remedy brominated organic pollutants in the environment.